Terbang Menuju Eksotisme Likupang - Rianandita Sari, Nanik; Fitriana Tungkagi, Sri Ariani; Fadhila, Olivia Shely; Mandraeny, Indryana (Sekolah Tinggi Teknologi Kedirgantaraan, 2025)
Sam Ratulangi airports in Manado contribute to the tourism industry by offering facilities and high-quality services. They promote local attractions and work well with various travel agents, which contributes to the growth of the tourism industry. Growing the transportation industry benefits both the economy and the travel and tourism industry. The research aims to analyze the tourism promotion strategies through Sam Ratulangi Airport. This is a descriptive analysis study using a qualitative technique. Sam Ratulangi International Airport is an international airport located 13 kilometers northeast of Manado, the capital of North Sulawesi in Indonesia. Using the SWOT matrix analysis, several different strategies for boosting nomadic tourism in Manado can be developed through the gate of Sam Ratulangi Airport. The results of the data will be used to determine the strengths, weaknesses, opportunities and threats of tourism objects in Sam Ratulangi Airport. The conclusion of this study states that for the tourism development strategy of Sam Ratulangi Airport, they are (1) improving the quality of facilities and infrastructure that supports tourism, (2) increasing tourism activities on a national and international scale, (3) promoting attractions on an ongoing basis to the national and international level, (4) developing various values of tourist attraction products, (5) involving the participation of the community and all interested parties in the management of attractions, and (6) improving the competency of human resources for tourism actors.